New mathematical approaches to the quantification of uncertainty affecting the measurement of U-value - De Simon, Lia (2017)
This thesis describes the development and validation of a new computational procedure for the calculation of thermal transmittance (U-value) of existing building elements from the measurement of surface heat flux, and surface and nearby air temperatures.